Compositional technique in Henry Purcell's consort music - Schab, Alon (Trinity College (Dublin, Ireland). Department of Music, 2011)
The research question: Most of the empirical evidence regarding Purcell's compositional process has not survived. The present study will seek to extract, using internal evidence in the music itself, information regarding Purcell's aesthetic priorities, compositional devices and order of work when, in his early twenties, he was engaged with the composition of the Fantazias for viols and the Sonatas a tre. The study will show that some compositional techniques that have not been explored in Purcell studies, especially palindromes and lists of pitches, were playing a significant part in Purcell's creative process. It will attempt to reconstruct several sages in Purcell's cmpositional process, and hence broaden our understanding of seventeenth-century musical creativity in general.
Keywords: Music, Ph.D.; Ph.D. Trinity College Dublin